2017
DOI: 10.1155/2017/1059216
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Binding of Cell Penetrating Peptides to siRNA: A Molecular Docking Study

Abstract: The use of gene therapeutics, including short interfering RNA (siRNA), is limited by the lack of efficient delivery systems. An appealing approach to deliver gene therapeutics involves noncovalent complexation with cell penetrating peptides (CPPs) which are able to penetrate the cell membranes of mammals. Although a number of CPPs have been discovered, our understanding of their complexation and translocation of siRNA is as yet insufficient. Here, we report on computational studies comparing the binding affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…Among various carriers, the CPP peptides are the potential delivery system for nucleic acids (Ignatovich et al, 2003; Järver et al, 2012; Shukla et al, 2014; Kizil et al, 2015). Forming protein-nucleic acid complex, CPPs can absorb on the surface of the double-stranded helix generally by electrostatic interaction, and such complexes can aggregate with size of up to 100 nm and have a positive charge (Rathnayake et al, 2017). CPPs were demonstrated as potential siRNA delivery systems for the suppression of gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various carriers, the CPP peptides are the potential delivery system for nucleic acids (Ignatovich et al, 2003; Järver et al, 2012; Shukla et al, 2014; Kizil et al, 2015). Forming protein-nucleic acid complex, CPPs can absorb on the surface of the double-stranded helix generally by electrostatic interaction, and such complexes can aggregate with size of up to 100 nm and have a positive charge (Rathnayake et al, 2017). CPPs were demonstrated as potential siRNA delivery systems for the suppression of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery molecules or vesicles help nucleic acids to cross biological barriers and prevent enzymatic degradation by endogenous nucleases. Besides the lipid-based delivery system, the polymer-based delivery system or inorganic nanoparticles, peptide carriers can be also used for nucleic acids transport into the cells (Zorko and Langel, 2005; Rathnayake et al, 2017). Among peptide carriers, the most promising are short amphipathic and cationic peptides, which translocate themselves across membranes and are collectively named as cell-penetrating peptides (CPP) (Hoyer and Neundorf, 2012; Morris and Labhasetwar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…CPPs, also referred to as protein transduction domains (PTD), can penetrate the plasma membrane of a cell and facilitate the delivery of various cargoes. Moreover, the cytotoxicity of CPPs is relatively low [ 115 ]. For instance, Tanaka et al reported stearic acid conjugated a CPP demonstrated that injecting STR-CH 2 R 4 H 2 C peptide with siVEGF suppressed the tumor growth efficiently compared with naked siRNA or controlled group [ 116 ].…”
Section: Membrane Impermeabilitymentioning
confidence: 99%
“…To date, a great variety of delivery system for siRNAs has been investigated such as lipids, polymers, aptamers and cell penetrating peptides (CPPs) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In this regard, CPPs appear as a new class of transporters, which increase intracellular uptake of biologically active molecules including siRNAs [ 45 ] ( Figure 2 ). Concerning hepatitis B virus infection, few or no studies are available currently on CPP-siRNAs targeting HBV.…”
Section: Benefit Of Cpps Used As Vehicles In Oligonucleotides Delimentioning
confidence: 99%